"Learning the hard way": Understanding the workplace learning of sports coach mentors - Leeder, T. M.; Russell, K.; Beaumont, L. C. (International Sport Coaching Journal, 2019)
The purpose of this study was to understand the workplace learning of sports coach mentors. Semi-structured interviews were conducted with 18 coach mentors employed by a sport governing body (SGB) as part of a formalised mentoring programme. `Current` coach mentors (n=9) had been employed for a minimum of one year by the organisation and were all interviewed once. `New` coach mentors (n=9) were all interviewed twice, once at the start of their employment and once again 9 months later. Moreover, regional mentors (n=8) who oversee the training and practice of the coach mentors participated in one focus group. Data were analysed thematically, with the sociology of Pierre Bourdieu and relevant workplace learning literature used to support the analytical process. The findings highlight how habitus structures coach mentors` participation in learning opportunities afforded to them in the workplace. In addition, habitus and embodied capital will impact how coach mentors interact with and interpret mentor training, whilst influencing their level of engagement with other employees. It is argued SGB social fields are crucial in the production of promoted norms and `legitimate` knowledge within workplaces, which subsequently influences mentor learning. Recommendations are made for critically transformative approaches to training coach mentors.